Babesia bigemina: Isolation and characterization of merozoite rhoptries - Machado, Rosangela Z. [UNESP]; McElwain, Terry F.; Suarez, Carlos E.; Hines, Stephen A.; Palmer, Guy H. (Elsevier, 1993)
Babesia bigemina apical membrane polypeptide p58, encoded by a multigene family with homologues in other Babesia spp. and sequence similarity to rhoptry proteins in other apicomplexan parasites, was identified within merozoite rhoptries using immunoelectron microscopy. To identify additional B. bigemina rhoptry proteins, rhoptries were isolated from French pressure cell-disrupted merozoites fractionated by differential centrifugation and isopycnic sucrose density gradient centrifugation. A fraction with a density of 1.16 g/ml contained club-shaped, electron-dense, membrane-bound organelles. Organelles were identified as rhoptries based on the following criteria: (i) density and morphology similar to those of rhoptries isolated from other apicomplexan parasites, (ii) dimensions similar to those of B. bigemina rhoptries in intact merozoites, and (iii) reactivity with an anti-p58 monoclonal antibody, but not with a monoclonal antibody against the merozoite outer membrane. Immunization of mice with isolated rhoptries induced antibodies that reacted with B. bigemina merozoites in an apical immunofluorescence pattern and bound the rhoptries in immunoelectron microscopy. Immunoprecipitation of [35S]methio-nine-labeled B. bigemina merozoites with the anti-rhoptry mouse serum identified at least seven putative rhoptry polypeptides including p58 (apparent molecular masses of >225, 190, 76, 69, 58, 54, 36 kDa). The anti-B. bigemina rhoptry serum did not immunoprecipitate any proteins from [35S]methionine-labeled Babesia bovis merozoites consistent with previous observations that members of the Babesia rhoptry gene families do not encode B-cell epitopes conserved between species. © 1993 Academic press, Inc.